A retrospective study of post-partum intrauterine contraceptive devices in a government maternity home of Delhi - Taneja, Neha; Gupta, Sujata; Kaur, Karuna N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Post-partum period is defined to be an ideal time for family planning counselling. Being a second largest populated country, India has a high rate of unintended pregnancy especially in post- partum women. There is a need for accessible, reliable contraception like post-partum intra uterine contraceptive device (PPIUCD) in our country. The present study is an attempt to evaluate the safety and efficacy of intra- uterine devices in post-partum women. Methods: The study population included all the women who delivered vaginally who were counselled for PPIUCD insertion in prenatal period, early labour and within 48 hours of delivery and were willing to participate in the study. Participants were interviewed prior to discharge after receiving a PPIUCD and then six, ten, fourteen weeks and 6 months or earlier when necessary. Institutional ethical approval and informed consent were taken. Results: A total of 1625 deliveries took place out of which only 888 were inserted PPIUCD. So, the total acceptance rate was 54.6%. Majority of cases were between the age group of 21-25 (46.4%) and most of them were primipara (39.8%). 34.8% came for routine follow up in OPD at 6 weeks, 14% at 6 months and 6.1% at 1 year. Conclusions: The IUCD insertion has been proved to be a safe and effective method of contraceptive with very few side effects and no major complications. To increase the knowledge and skills among health care providers, it is necessary to arrange training on PPIUCD.